Low-odor dry ceiling and manufacturing method thereof
By using low-odor dry process and composite activated carbon adsorbent in the car roof, the problem of VOC release during the production and use of the car roof is solved, and better air quality is achieved.
Patent Information
- Application Number
- CN202510033874.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The polymer organic matter produced during production and use of the car roof will release small molecular organic compounds (VOCs) that are volatile at low boiling points, resulting in a decrease in air quality in the car.
A low-odor dry roof is adopted, and its structure includes a non-woven fabric, chopped glass fiber layer, adsorption adhesive layer, hot melt adhesive film layer, polyurethane foam layer and fabric layer. Compound activated carbon is added to the adsorption adhesive layer, and the adsorption capacity to VOC is enhanced through the combination of microporous and mesoporous activated carbon and the modification of silica aerogel.
It effectively reduces the volatility of VOC in the car roof, reduces the odor in the car, and improves air quality.
Abstract
Description
Technical Field
[0001] The present application relates to the field of automobile ceilings, and more specifically, to a low-odor dry-process ceiling and a manufacturing method thereof. Background Art
[0002] Dry process automobile ceilings are widely used because of their excellent dimensional stability, sound absorption and heat insulation performance under long-term use in high temperature, high temperature and high humidity, extremely cold weather and other environments. The dry process ceiling frame forming and fabric lamination only use one set of molds, which can reduce the investment of one set of molds and reduce manufacturing costs compared to the wet process ceiling.
[0003] With the development of the automobile industry, users' requirements for various aspects of automobiles are gradually increasing. Various low-boiling-point volatile small-molecule organic compounds, referred to as VOCs, in new cars may cause headaches, nausea, vomiting, fatigue, etc., and may cause damage to the liver, kidneys, brain and nervous system. Therefore, the air quality in the car has become an important indicator for people to buy cars. The high-molecular organic matter used in the production process of the car roof will produce VOCs during the production and use process, which reduces the air quality in the car. Summary of the invention
[0004] In order to reduce odor and VOC during the production and use of automobile ceilings, the present application provides a low-odor dry ceiling and a method for making the same.
[0005] In the first aspect, the present application provides a low-odor dry ceiling, which adopts the following technical solution: A low-odor dry ceiling comprises a non-woven fabric, a first chopped glass fiber layer, a first adsorption adhesive layer, a first hot melt adhesive film layer, a polyurethane foam layer, a second chopped glass fiber layer, a second adsorption adhesive layer, a second hot melt adhesive film layer, and a fabric layer connected in sequence; The first adsorption bonding layer and the second adsorption bonding layer both include high-density polyethylene powder and an adsorbent, wherein the amount of the adsorbent added is 15-25wt% of the high-density polyethylene powder, and the adsorbent is a composite activated carbon modified with silica aerogel, wherein the composite activated carbon includes microporous activated carbon and mesoporous activated carbon in a mass ratio of (2.56-3.12):(1.12-2.05).
[0006] By adopting the above technical scheme, adsorbent is added to the first adsorption adhesive layer and the second adsorption adhesive layer, and the composite activated carbon contained in the adsorbent is composited by microporous activated carbon and mesoporous activated carbon. The microporous activated carbon and the mesoporous activated carbon have different pore diameters and can adsorb organic matter of different molecular weights in VOC, thereby broadening the adsorption range of the composite adsorbent and improving the adsorption efficiency and adsorption amount of volatile substances of different molecular weights by the composite adsorbent. The silica aerogel has a higher porosity and better air permeability, thereby increasing the contact area between the adsorbent and VOC.
[0007] Preferably, the preparation method of the microporous activated carbon comprises the following steps: heating the coconut shell to 275-285°C at 1.5-2°C / min in an oxygen-nitrogen mixed gas, cooling to room temperature after keeping warm for 1-1.2h to complete pre-oxidation, introducing nitrogen, heating to 245-255°C at 2.5-3°C / min, heating to 650-660°C at 2.5-3°C / min, carbonizing for 1-1.2h, cooling to room temperature, heating to 800-850°C at 8-10°C / min, activating for 4-4.5h to obtain microporous activated carbon.
[0008] By adopting the above technical scheme, the coconut shell is pre-oxidized, the primary hydroxyl groups in the coconut shell that are easy to break the main chain are oxidized, and the cellulose and hemicellulose in the coconut shell are oxidized, thereby improving the stability of the structure and increasing the content of oxygen-containing groups in the microporous activated carbon, which is beneficial to improving the adsorption efficiency of the microporous activated carbon for VOCs.
[0009] Preferably, the preparation method of the mesoporous activated carbon comprises the following steps: carbonizing the coconut shell fiber at 400-500°C and taking it out, adding a mixed powder of potassium hydroxide and sodium hydroxide, mixing evenly, heating to 850-900°C at 5-10°C / min, and activating for 150 minutes to obtain the mesoporous activated carbon.
[0010] By adopting the above technical solution, the prepared mesoporous activated carbon has more mesopores, can adsorb substances with larger molecular weight in VOC, and provide channels for micropore adsorption, thereby improving the adsorption effect of the composite activated carbon.
[0011] Preferably, the preparation method of the silica aerogel-modified composite activated carbon comprises the following steps: mixing microporous activated carbon with mesoporous activated carbon by ball milling to obtain composite activated carbon for standby use; mixing tetraethyl orthosilicate, ethanol and water, adding dilute hydrochloric acid to adjust the pH to 4-4.5, heating to 45-50°C and stirring for 60-65 minutes, adding ammonia water to adjust the pH to neutral, stirring for 55-60 minutes to obtain a mixed solution, adding the mixed solution to the composite activated carbon, ultrasonicating for 3-5 minutes and then standing to form a wet gel; and aging, replacing and freeze-drying the wet gel to obtain a silica aerogel-modified composite activated carbon.
[0012] By adopting the above technical scheme, the surface of the composite activated carbon is uniformly coated with silica aerogel, thereby realizing the modification of the composite activated carbon by silica aerogel. The silica aerogel has a high porosity and good air permeability, which increases the contact area between the adsorbent and VOC and increases the diffusion rate of VOC, which is beneficial to improving the adsorption efficiency and adsorption effect of the adsorbent.
[0013] Preferably, the added amount of the composite activated carbon is 10.25-11.92wt% of the mixed solution.
[0014] By adopting the above technical solution, the addition amount of the composite activated carbon is controlled so that the silica aerogel can evenly coat the composite activated carbon, while not easily blocking more pores of the composite activated carbon, thereby maintaining the adsorption effect of the adsorbent.
[0015] Preferably, before the mixed solution is added to the activated carbon, the following operation is further performed: adding a composite biological enzyme to the mixed solution, wherein the amount of the composite biological enzyme added is 4.52-5.98wt% of the mixed solution.
[0016] By adopting the above technical solution, the composite biological enzyme can biodegrade the VOC adsorbed by the adsorbent, so that the adsorbent can continuously adsorb the VOC for a long time. At the same time, the composite biological enzyme is coated with silica aerogel and is less affected by environmental factors, which is conducive to maintaining the activity and decomposition efficiency of the composite biological enzyme.
[0017] Preferably, the composite biological enzyme comprises formaldehyde dehydrogenase and formate dehydrogenase in a mass ratio of (1.25-1.65):(0.98-1.16).
[0018] By adopting the above technical solution and using formaldehyde dehydrogenase and formate dehydrogenase in combination, formaldehyde can be effectively decomposed and harmlessly treated, which is beneficial to improving the adsorption effect of the adsorbent on VOC.
[0019] In a second aspect, the present application provides a method for preparing a low-odor dry ceiling, using the following technical solution: A method for preparing a low-odor dry ceiling comprises the following steps: The first chopped glass fiber is sequentially cut and spread on the non-woven fabric, the raw material of the first adsorption adhesive layer is spread, the first hot melt adhesive film layer is unwound, the polyurethane foam layer is placed, the second chopped glass fiber layer is cut and spread, the raw material of the second adsorption adhesive layer is spread, the second hot melt adhesive film layer is unwound, infrared preheating is performed, the upper heating plate is heated to 190-210° C., the lower heating plate is heated to 200-220° C., roller pressing and compounding are performed under a pressure of 0.3-0.5 MPa, and a sandwich substrate is obtained after cooling; The sandwich substrate is heated in a preheating furnace with an upper heating plate at 190-210°C and a lower heating plate at 200-220°C for 27-33s, and then heated in a heating furnace with an upper heating plate at 200-220°C and a lower heating plate at 210-230°C for 27-33s, and is molded with the fabric to obtain a ceiling prototype with a holding pressure of 77-83 bar and a holding time of 27-33s. After cutting, sorting and edge wrapping, the ceiling prototype is obtained to obtain a low-odor dry ceiling.
[0020] By adopting the above technical solution, the obtained car ceiling has less VOC volatility and less odor, which can effectively improve the air quality inside the car.
[0021] In summary, this application has the following beneficial effects: 1. Since adsorbents are added to the first adsorption adhesive layer and the second adsorption adhesive layer in the present application, the composite activated carbon contained in the adsorbent is composited by microporous activated carbon and mesoporous activated carbon. The microporous activated carbon and the mesoporous activated carbon have different pore diameters and can adsorb organic matter of different molecular weights in VOCs, thereby broadening the adsorption range of the composite adsorbent and improving the adsorption efficiency and adsorption amount of volatile substances of different molecular weights by the composite adsorbent. The silica aerogel has a high porosity and good air permeability, which increases the contact area between the adsorbent and the VOC.
[0022] 2. In the present application, the surface of the composite activated carbon is uniformly coated with silica aerogel, thereby realizing the modification of the composite activated carbon by silica aerogel. The silica aerogel has a high porosity and good air permeability, which increases the contact area between the adsorbent and VOC and increases the diffusion rate of VOC, which is beneficial to improving the adsorption efficiency and adsorption effect of the adsorbent.
[0023] 3. The composite biological enzyme in the present application can biodegrade the VOC adsorbed by the adsorbent, so that the adsorbent can continuously adsorb the VOC for a long time. At the same time, the composite biological enzyme is coated with silica aerogel and is less affected by environmental factors, which is conducive to maintaining the activity and decomposition efficiency of the composite biological enzyme. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with embodiments.
[0025] In the preparation examples of the present application, formaldehyde dehydrogenase and formate dehydrogenase were purchased from Shanghai Yuanye Biotechnology Co., Ltd. The formaldehyde dehydrogenase model was S25151-100U, and the formate dehydrogenase model was S25081-250u. Preparation Examples 1-4 of Microporous Activated Carbon
[0026] Preparation Example 1 The preparation method of microporous activated carbon comprises the following steps: heating coconut shell to 275°C at 1.5°C / min in an oxygen-nitrogen mixed gas with an oxygen volume fraction of 5%, keeping the temperature for 1.2 hours and then cooling to room temperature to complete pre-oxidation, introducing nitrogen, heating to 245°C at 2.5°C / min, then heating to 650°C at 2.5°C / min, carbonizing for 1.2 hours and then cooling to room temperature, heating to 850°C at 8°C / min, activating for 4 hours to obtain microporous activated carbon.
[0027] Preparation Example 2 The preparation method of microporous activated carbon comprises the following steps: heating coconut shell to 285°C at 2°C / min in an oxygen-nitrogen mixed gas with an oxygen volume fraction of 5%, keeping the temperature for 1 hour and then cooling to room temperature to complete pre-oxidation, introducing nitrogen, heating to 255°C at 3°C / min, then heating to 660°C at 3°C / min, carbonizing for 1 hour and then cooling to room temperature, heating to 900°C at 10°C / min, activating for 4.5 hours to obtain microporous activated carbon.
[0028] Preparation Example 3 The preparation method of microporous activated carbon comprises the following steps: heating coconut shell to 275°C at 2°C / min in an oxygen-nitrogen mixed gas with an oxygen volume fraction of 5%, keeping the temperature for 1 hour and then cooling to room temperature to complete pre-oxidation, introducing nitrogen, heating to 255°C at 2.5°C / min, then heating to 650°C at 3°C / min, carbonizing for 1.2 hours and then cooling to room temperature, heating to 850°C at 9°C / min, activating for 4 hours to obtain microporous activated carbon.
[0029] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 3 is that in Preparation Example 4, the coconut shell is not subjected to pre-oxidation treatment. Preparation Example 5-9 of Mesoporous Activated Carbon
[0030] Preparation Example 5 The preparation method of mesoporous activated carbon comprises the following steps: carbonizing coconut shell fiber at 400°C and taking it out, adding a mixed powder of potassium hydroxide and sodium hydroxide, mixing evenly, heating to 850°C at 5°C / min, and activating for 150min to obtain mesoporous activated carbon, wherein the mass ratio of the carbonized coconut shell fiber, potassium hydroxide and sodium hydroxide is 1:1:4.
[0031] Preparation Example 6 The preparation method of mesoporous activated carbon comprises the following steps: carbonizing coconut shell fiber at 500°C and taking it out, adding a mixed powder of potassium hydroxide and sodium hydroxide, mixing evenly, heating to 900°C at 10°C / min, and activating for 150min to obtain mesoporous activated carbon, wherein the mass ratio of the carbonized coconut shell fiber, potassium hydroxide and sodium hydroxide is 1:1:3.
[0032] Preparation Example 7 The preparation method of mesoporous activated carbon comprises the following steps: carbonizing coconut shell fiber at 400-500°C and taking it out, adding a mixed powder of potassium hydroxide and sodium hydroxide, mixing evenly, heating to 870°C at 8°C / min, and activating for 150min to obtain mesoporous activated carbon, wherein the mass ratio of the carbonized coconut shell fiber, potassium hydroxide and sodium hydroxide is 1:1:3.5.
[0033] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 5 is that in Preparation Example 8, the mass ratio of carbonized coconut shell fiber, potassium hydroxide and sodium hydroxide is 1:1:1.
[0034] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 5 is that in Preparation Example 9, the mass ratio of carbonized coconut shell fiber, potassium hydroxide and sodium hydroxide is 1:1:8. Preparation Example 10-25 of Silica Aerogel Modified Composite Activated Carbon
[0035] Preparation Example 10 The preparation method of composite activated carbon modified by silica aerogel comprises the following steps: ball-milling and mixing microporous activated carbon and mesoporous activated carbon in a mass ratio of 2.56:1.12 to prepare composite activated carbon for standby use, wherein the microporous activated carbon is the microporous activated carbon prepared in Preparation Example 1, and the mesoporous activated carbon is the mesoporous activated carbon prepared in Preparation Example 5; After mixing tetraethyl orthosilicate, ethanol and water in a molar ratio of 0.8:17.5:4.2, 1wt% dilute hydrochloric acid was added to adjust the pH to 4, the temperature was raised to 45°C and stirred for 65 minutes, 10wt% ammonia water was added to adjust the pH to neutral, and the mixture was stirred for 60 minutes to obtain a mixed solution, to which composite activated carbon was added in an amount of 10.25wt% of the mixed solution. After ultrasonication for 3 minutes, the mixture was allowed to stand to form a wet gel. After aging, replacement and freeze-drying of the wet gel, a silica aerogel-modified composite activated carbon was obtained.
[0036] Preparation Example 11 The preparation method of composite activated carbon modified by silica aerogel comprises the following steps: ball-milling and mixing microporous activated carbon and mesoporous activated carbon in a mass ratio of 3.12:2.05 to prepare composite activated carbon for standby use, wherein the microporous activated carbon is the microporous activated carbon prepared in Preparation Example 2, and the mesoporous activated carbon is the mesoporous activated carbon prepared in Preparation Example 6; After mixing tetraethyl orthosilicate, ethanol and water in a molar ratio of 1.2:17:3.5, 1wt% dilute hydrochloric acid was added to adjust the pH to 4.5, the temperature was raised to 50°C and stirred for 60 minutes, 10wt% ammonia water was added to adjust the pH to neutral, and the mixture was stirred for 55-60 minutes to obtain a mixed solution, to which composite activated carbon was added in an amount of 11.92wt% of the mixed solution, and the mixture was ultrasonicated for 5 minutes and allowed to stand to form a wet gel. The wet gel was aged, replaced and freeze-dried to obtain a composite activated carbon modified with silica aerogel.
[0037] Preparation Example 12 The preparation method of composite activated carbon modified by silica aerogel comprises the following steps: ball-milling and mixing microporous activated carbon and mesoporous activated carbon with a mass ratio of 2.89:1.85 to obtain composite activated carbon for standby use, wherein the microporous activated carbon is the microporous activated carbon obtained in Preparation Example 3, and the mesoporous activated carbon is the mesoporous activated carbon obtained in Preparation Example 7. After mixing tetraethyl orthosilicate, ethanol and water in a molar ratio of 1.1:18:3.8, 1wt% dilute hydrochloric acid was added to adjust the pH to 4.3, the temperature was raised to 45°C and stirred for 60 minutes, 10wt% ammonia water was added to adjust the pH to neutral, and the mixture was stirred for 55 minutes to obtain a mixed solution, to which composite activated carbon was added in an amount of 11.13wt% of the mixed solution. After ultrasonic treatment for 4 minutes, the mixture was allowed to stand to form a wet gel. After aging, replacement and freeze-drying of the wet gel, a silica aerogel-modified composite activated carbon was obtained.
[0038] Preparation Example 13 The difference between Preparation Example 13 and Preparation Example 10 is that in Preparation Example 13, the mass ratio of microporous activated carbon to mesoporous activated carbon is 2.56:0.53.
[0039] Preparation Example 14 The difference between Preparation Example 14 and Preparation Example 10 is that in Preparation Example 14, the mass ratio of microporous activated carbon to mesoporous activated carbon is 2.56:3.56.
[0040] Preparation Example 15 The difference between Preparation Example 15 and Preparation Example 10 is that in Preparation Example 15, the addition amount of the composite activated carbon is 8.25 wt % of the mixed solution.
[0041] Preparation Example 16 The difference between Preparation Example 16 and Preparation Example 10 is that in Preparation Example 16, the amount of composite activated carbon added is 14.98 wt % of the mixed solution.
[0042] Preparation Example 17 The difference between Preparation Example 17 and Preparation Example 10 is that in Preparation Example 17, the microporous activated carbon is the microporous activated carbon prepared in Preparation Example 4.
[0043] Preparation Example 18 The difference between Preparation Example 18 and Preparation Example 10 is that in Preparation Example 18, the mesoporous activated carbon is the mesoporous activated carbon prepared in Preparation Example 8.
[0044] Preparation Example 19 The difference between Preparation Example 19 and Preparation Example 10 is that in Preparation Example 19, the mesoporous activated carbon is the mesoporous activated carbon prepared in Preparation Example 9.
[0045] Preparation Example 20 The difference between Preparation Example 20 and Preparation Example 10 is that in Preparation Example 20, before the composite activated carbon is added to the mixed solution, the following operations are also performed: a composite biological enzyme is added to the mixed solution, the amount of the composite biological enzyme added is 4.52wt% of the mixed solution, and the composite biological enzyme includes formaldehyde dehydrogenase and formate dehydrogenase in a mass ratio of 1.25:0.98.
[0046] Preparation Example 21 The difference between Preparation Example 21 and Preparation Example 10 is that in Preparation Example 21, before the composite activated carbon is added to the mixed solution, the following operations are also performed: a composite biological enzyme is added to the mixed solution, and the amount of the composite biological enzyme added is 5.98wt% of the mixed solution. The composite biological enzyme includes formaldehyde dehydrogenase and formate dehydrogenase in a mass ratio of 1.65:-1.16.
[0047] Preparation Example 22 The difference between Preparation Example 22 and Preparation Example 20 is that in Preparation Example 22, the composite biological enzyme includes formaldehyde dehydrogenase and formate dehydrogenase in a mass ratio of 1.25:0.54.
[0048] Preparation Example 23 The difference between Preparation Example 23 and Preparation Example 20 is that in Preparation Example 23, the composite biological enzyme includes formaldehyde dehydrogenase and formate dehydrogenase in a mass ratio of 1.25:2.98.
[0049] Preparation Example 24 The difference between Preparation Example 24 and Preparation Example 20 is that in Preparation Example 24, an equal amount of formaldehyde dehydrogenase is used instead of the composite biological enzyme.
[0050] Preparation Example 25 The difference between Preparation Example 25 and Preparation Example 20 is that in Preparation Example 25, an equal amount of formate dehydrogenase is used instead of the composite biological enzyme. Example
[0051] In the embodiment of the present application, the chopped glass fibers used in the first chopped glass fiber layer and the second chopped glass fiber layer are 1-2 inches in length, and the hot melt adhesive raw materials and high-density polyethylene powder used in the first hot melt adhesive film layer, the second hot melt adhesive film layer, the first adsorption bonding layer and the second adsorption bonding layer are all high-density polyethylene of LG Chemical, model ME9180R.
[0052] Example 1 A low-odor dry ceiling comprises a non-woven fabric, a first chopped glass fiber layer, a first adsorption adhesive layer, a first hot melt adhesive film layer, a polyurethane foam layer, a second chopped glass fiber layer, a second adsorption adhesive layer, a second hot melt adhesive film layer, and a fabric layer connected in sequence; The first adsorption adhesive layer and the second adsorption adhesive layer both include high-density polyethylene powder and an adsorbent. The added amount of the adsorbent is 15wt% of the high-density polyethylene powder. The adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 10.
[0053] The method for manufacturing the low-odor dry ceiling comprises the following steps: The first short glass fiber is cut and spread on the non-woven fabric in sequence, the raw material of the first adsorption adhesive layer is spread, the first hot melt adhesive film layer is unwound, the polyurethane foam layer is placed, the second short glass fiber layer is cut and spread, the raw material of the second adsorption adhesive layer is spread, the second hot melt adhesive film layer is unwound, infrared preheating is performed, the upper heating plate is heated to 190° C., the lower heating plate is heated to 200° C., roller pressing and compounding are performed under a pressure of 0.5 MPa, and a sandwich substrate is obtained after cooling; The sandwich substrate is heated in a preheating furnace with an upper heating plate of 190°C and a lower heating plate of 200°C for 33 seconds, and then heated in a heating furnace with an upper heating plate of 200°C and a lower heating plate of 210°C for 33 seconds, and is molded with the fabric to obtain a ceiling prototype with a holding pressure of 83 bar and a holding time of 33 seconds. After cutting, sorting, and edge wrapping, a low-odor dry ceiling is obtained.
[0054] Example 2 A low-odor dry ceiling comprises a non-woven fabric, a first chopped glass fiber layer, a first adsorption adhesive layer, a first hot melt adhesive film layer, a polyurethane foam layer, a second chopped glass fiber layer, a second adsorption adhesive layer, a second hot melt adhesive film layer, and a fabric layer connected in sequence; The first adsorption adhesive layer and the second adsorption adhesive layer both include high-density polyethylene powder and an adsorbent. The added amount of the adsorbent is 25wt% of the high-density polyethylene powder. The adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 11.
[0055] The method for manufacturing the low-odor dry ceiling comprises the following steps: The first short glass fiber is cut and spread on the non-woven fabric in sequence, the raw material of the first adsorption adhesive layer is spread, the first hot melt adhesive film layer is unwound, the polyurethane foam layer is placed, the second short glass fiber layer is cut and spread, the raw material of the second adsorption adhesive layer is spread, the second hot melt adhesive film layer is unwound, infrared preheating is performed, the upper heating plate is heated to 210° C., the lower heating plate is heated to 220° C., roller pressing and compounding are performed under a pressure of 0.3 MPa, and the sandwich substrate is obtained after cooling; The sandwich substrate is heated in a preheating furnace with an upper heating plate of 210°C and a lower heating plate of 220°C for 27 seconds, and then heated in a heating furnace with an upper heating plate of 220°C and a lower heating plate of 230°C for 27 seconds, and is molded with the fabric to obtain a ceiling prototype with a holding pressure of 77 bar and a holding time of 27 seconds. After cutting, sorting, and edge wrapping, a low-odor dry ceiling is obtained.
[0056] Example 3 A low-odor dry ceiling comprises a non-woven fabric, a first chopped glass fiber layer, a first adsorption adhesive layer, a first hot melt adhesive film layer, a polyurethane foam layer, a second chopped glass fiber layer, a second adsorption adhesive layer, a second hot melt adhesive film layer, and a fabric layer connected in sequence; The first adsorption adhesive layer and the second adsorption adhesive layer both include high-density polyethylene powder and an adsorbent. The added amount of the adsorbent is 20wt% of the high-density polyethylene powder. The adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 12.
[0057] The method for manufacturing the low-odor dry ceiling comprises the following steps: The first short glass fiber is cut and spread on the non-woven fabric in sequence, the raw material of the first adsorption adhesive layer is spread, the first hot melt adhesive film layer is unwound, the polyurethane foam layer is placed, the second short glass fiber layer is cut and spread, the raw material of the second adsorption adhesive layer is spread, the second hot melt adhesive film layer is unwound, infrared preheating is performed, the upper heating plate is heated to 200° C., the lower heating plate is heated to 210° C., roller pressing and compounding are performed under a pressure of 0.4 MPa, and a sandwich substrate is obtained after cooling; The sandwich substrate is heated in a preheating furnace with an upper heating plate of 200°C and a lower heating plate of 210°C for 30 seconds, and then heated in a heating furnace with an upper heating plate of 210°C and a lower heating plate of 220°C for 30 seconds, and is molded with the fabric to obtain a ceiling prototype with a holding pressure of 80 bar and a holding time of 30 seconds. After cutting, sorting, and edge wrapping, the ceiling prototype is obtained to obtain a low-odor dry ceiling.
[0058] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 15.
[0059] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 16.
[0060] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 17.
[0061] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 18.
[0062] Example 8 The difference between Example 8 and Example 1 is that in Example 8, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 19.
[0063] Example 9 The difference between Example 9 and Example 1 is that in Example 9, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 20.
[0064] Example 10 The difference between Example 10 and Example 1 is that in Example 10, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 21.
[0065] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 22.
[0066] Example 12 The difference between Example 12 and Example 1 is that in Example 12, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 23.
[0067] Embodiment 13 The difference between Example 13 and Example 1 is that in Example 13, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 24.
[0068] Embodiment 14 The difference between Example 14 and Example 1 is that in Example 14, the adsorbent is the composite activated carbon modified with silica aerogel obtained in Preparation Example 25. Comparative Example
[0069] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the adsorbent is the composite activated carbon modified with silica aerogel prepared in Preparation Example 13.
[0070] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the adsorbent is the composite activated carbon modified with silica aerogel prepared in Preparation Example 14.
[0071] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, no adsorbent is added to the first adsorption adhesive layer and the second adsorption adhesive layer.
[0072] Test methods The ceilings prepared in Examples 1-14 and Comparative Examples 1-3 were used as samples with a sample size of 1.7m×1.2m×6mm. Thermal desorption gas mass spectrometer and high performance liquid chromatography were used to detect the release of formaldehyde, xylene and total volatile organic compounds in the samples, and the results were recorded in Table 1.
[0073] Table 1 VOC detection of samples project <![CDATA[Formaldehyde / (μg / m 3 )]]> <![CDATA[Toluene / (μg / m 3 )]]> <![CDATA[Total volatile organic compounds / (μg / m 3 )]]> Example 1 22.26 82.25 253.15 Example 2 20.92 79.34 246.58 Example 3 21.62 80.83 249.34 Example 4 25.98 88.54 264.12 Example 5 25.24 87.35 263.42 Example 6 26.21 85.47 256.91 Example 7 25.31 89.34 259.24 Example 8 26.08 88.29 261.43 Example 9 18.12 73.98 234.61 Example 10 16.48 70.26 230.54 Embodiment 11 22.25 85.31 254.34 Example 12 22.63 84.28 253.28 Embodiment 13 23.18 85.43 255.54 Embodiment 14 23.47 86.01 254.61 Comparative Example 1 15.42 95.92 276.28 Comparative Example 2 27.62 71.67 268.62 Comparative Example 3 29.31 82.15 287.43 According to Examples 1-3, Comparative Example 3 and Table 1, it can be seen that the automobile ceilings prepared in Examples 1-3 have lower VOC and less odor when used. Adsorbents are added to the first adsorption adhesive layer and the second adsorption adhesive layer. The composite activated carbon is composed of microporous activated carbon and mesoporous activated carbon. The adsorbent is modified by silica aerogel. The microporous activated carbon and the mesoporous activated carbon have pore diameters of different sizes and can adsorb VOCs of different molecular weights respectively. The composite use of microporous activated carbon and mesoporous activated carbon can effectively improve the absorption efficiency and absorption effect of VOCs, and broaden the adsorption range of the composite adsorbent. The silica aerogel has a higher porosity and better air permeability, which increases the contact area between the adsorbent and VOC. At the same time, the silica aerogel has a higher porosity and air permeability, which can improve the diffusion efficiency of VOCs and increase the contact area between the adsorbent and VOC, thereby further improving the adsorption efficiency and adsorption effect of the adsorbent and reducing the volatilization of VOCs.
[0074] Compared with Example 1-3, the VOC content of the car ceiling prepared in Example 4-5 is improved. When preparing the adsorbent in Example 4-5, the addition amount of the composite activated carbon in the mixed solution is changed, which directly affects the coating of the silica aerogel on the surface of the composite activated carbon. When the addition amount is small, the deposition amount of silica aerogel is large, and the pores of the composite activated carbon are easily blocked in large quantities, thereby reducing the adsorption effect of the adsorbent. When the addition amount is large, the coating of the silica aerogel is uneven and incomplete, which affects the modification of the silica aerogel, thereby reducing the adsorption effect of the adsorbent.
[0075] Compared with Examples 1-3, the VOC content of the car ceiling prepared in Example 6 is increased. When preparing the adsorbent in Example 6, the microporous activated carbon has not undergone pre-oxidation treatment. The pre-oxidation treatment can oxidize the cellulose and hemicellulose in the coconut shell, and at the same time oxidize the primary hydroxyl groups to increase the proportion of micropores in the activated carbon. The adsorbent used in Example 6 has not undergone pre-oxidation treatment, the micropore proportion is reduced, and the adsorption effect on small molecular weight VOCs such as formaldehyde is weakened.
[0076] Compared with Examples 1-3, the VOC content of the car ceiling prepared in Example 7-8 is improved. When preparing the mesoporous activated carbon in Example 7-8, the mass ratio of the carbonized coconut shell fiber, potassium hydroxide and sodium hydroxide is changed, the activated carbon is activated by potassium hydroxide and sodium hydroxide, and the activated carbon is corroded by alkaline vapor, thereby increasing the mesopore ratio of the activated carbon. The combination of potassium hydroxide and sodium hydroxide has a synergistic effect, which can further increase the mesopore content, thereby improving the adsorption efficiency of the mesoporous activated carbon for VOCs with larger molecular weight. However, in Example 7-8, the ratio of potassium hydroxide and sodium hydroxide is adjusted, the synergistic effect is weakened, the mesopore ratio of the mesoporous activated carbon is reduced, and the adsorption effect is weakened.
[0077] Compared with Examples 1-3, the VOC content of the car ceiling prepared in Examples 9-10 is reduced. When preparing the adsorbent in Examples 9-10, a composite biological enzyme is added to the mixed solution. The composite biological enzyme is coated with silica aerogel and attached to the surface of the composite activated carbon. The composite biological enzyme can biodecompose the VOC adsorbed by the adsorbent, so that the adsorbent can continuously adsorb VOC for a long time. Moreover, the composite biological enzyme is coated by silica gas condensation and is less affected by external environmental factors. It can effectively maintain the activity and decomposition efficiency of the composite biological enzyme, thereby improving the adsorption efficiency of the adsorbent for VOC.
[0078] Compared with Examples 9-10, the VOC content of the car ceiling prepared in Example 11-14 is improved. When preparing the adsorbent in Example 11-12, the mass ratio of formaldehyde dehydrogenase and formate dehydrogenase in the composite biological enzyme is changed. In Example 13, only formaldehyde dehydrogenase is added, and in Example 14, only formate dehydrogenase is added. This shows that formaldehyde dehydrogenase and formate dehydrogenase are used in combination according to the mass ratio, which has a synergistic effect and can effectively decompose and harmlessly treat the VOC adsorbed by the adsorbent, thereby improving the adsorption efficiency and adsorption effect of the adsorbent on VOC, and can extend the service life of the adsorbent.
[0079] Compared with Examples 1-3, the VOC content of the car roof prepared in Comparative Example 1-2 is improved. When preparing the adsorbent in Comparative Example 1-2, the mass ratio of microporous activated carbon to mesoporous activated carbon is changed. If the adsorbent is added in too much amount, agglomeration is likely to occur. When the amount of adsorbent added is limited, the microporous activated carbon and mesoporous activated carbon are composited in a mass ratio, and the adsorption performance of VOC on the car roof is better, and VOCs of different molecular weights can be adsorbed more comprehensively and efficiently, thereby improving air quality and reducing VOC volatilization.
[0080] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A low-odor dry ceiling, characterized in that: It includes a non-woven fabric, a first chopped glass fiber layer, a first adsorption bonding layer, a first hot melt adhesive film layer, a polyurethane foam layer, a second chopped glass fiber layer, a second adsorption bonding layer, a second hot melt adhesive film layer, and a fabric layer connected in sequence; The first adsorption bonding layer and the second adsorption bonding layer both include high-density polyethylene powder and an adsorbent, wherein the amount of the adsorbent added is 15-25wt% of the high-density polyethylene powder, and the adsorbent is a composite activated carbon modified with silica aerogel, wherein the composite activated carbon includes microporous activated carbon and mesoporous activated carbon in a mass ratio of (2.56-3.12):(1.12-2.05).
2. A low-odor dry ceiling according to claim 1, characterized in that: The preparation method of microporous activated carbon comprises the following steps: heating coconut shell to 275-285°C at 1.5-2°C / min in oxygen-nitrogen mixed gas, cooling to room temperature after keeping the temperature for 1-1.2h, completing pre-oxidation, introducing nitrogen, heating to 245-255°C at 2.5-3°C / min, heating to 650-660°C at 2.5-3°C / min, carbonizing for 1-1.2h, cooling to room temperature, heating to 850-900°C at 8-10°C / min, activating for 4-4.5h, and obtaining microporous activated carbon.
3. The low-odor dry ceiling according to claim 1, characterized in that: The preparation method of mesoporous activated carbon comprises the following steps: carbonizing coconut shell fiber at 400-500°C and taking it out, adding mixed powder of potassium hydroxide and sodium hydroxide, mixing evenly, heating to 850-900°C at 5-10°C / min, activating for 150min, and preparing mesoporous activated carbon.
4. The low-odor dry ceiling according to claim 1, characterized in that: The preparation method of composite activated carbon modified by silica aerogel comprises the following steps: mixing microporous activated carbon and mesoporous activated carbon by ball milling to obtain composite activated carbon for standby use; mixing tetraethyl orthosilicate, ethanol and water, adding dilute hydrochloric acid to adjust the pH value to 4-4.5, heating to 45-50°C and stirring for 60-65 minutes, adding ammonia water to adjust the pH value to neutral, stirring for 55-60 minutes to obtain a mixed solution, adding composite activated carbon to the mixed solution, ultrasonicating for 3-5 minutes and then standing to form a wet gel; and aging, replacing and freeze-drying the wet gel to obtain composite activated carbon modified by silica aerogel.
5. The low-odor dry ceiling according to claim 4, characterized in that: The added amount of the composite activated carbon is 10.25-11.92wt% of the mixed solution.
6. The low-odor dry ceiling according to claim 4, characterized in that: Before adding the composite activated carbon to the mixed solution, the following operation is also performed: adding a composite biological enzyme to the mixed solution, wherein the amount of the composite biological enzyme added is 4.52-5.98wt% of the mixed solution.
7. The low-odor dry ceiling according to claim 6, characterized in that: The composite biological enzyme comprises formaldehyde dehydrogenase and formate dehydrogenase in a mass ratio of (1.25-1.65):(0.98-1.16).
8. The method for manufacturing a low-odor dry ceiling according to any one of claims 1 to 7, characterized in that: The following steps are involved: The first chopped glass fiber is sequentially cut and spread on the non-woven fabric, the raw material of the first adsorption adhesive layer is spread, the first hot melt adhesive film layer is unwound, the polyurethane foam layer is placed, the second chopped glass fiber layer is cut and spread, the raw material of the second adsorption adhesive layer is spread, the second hot melt adhesive film layer is unwound, infrared preheating is performed, the upper heating plate is heated to 190-210° C., the lower heating plate is heated to 200-220° C., roller pressing and compounding are performed under a pressure of 0.3-0.5 MPa, and a sandwich substrate is obtained after cooling; The sandwich substrate is heated in a preheating furnace with an upper heating plate at 190-210°C and a lower heating plate at 200-220°C for 27-33s, and then heated in a heating furnace with an upper heating plate at 200-220°C and a lower heating plate at 210-230°C for 27-33s, and is molded with the fabric to obtain a ceiling prototype with a holding pressure of 77-83 bar and a holding time of 27-33s. After cutting, sorting and edge wrapping, the ceiling prototype is obtained to obtain a low-odor dry ceiling.
Citation Information
Patent Citations
Low VOC automobile upholstery roof material and preparation method thereof
CN107538834A
Preparation method of composite aerogel material and application of composite aerogel material in water purification
CN117753364A
Organic aerogels reinforced with inorganic aerogel fillers
US20070259979A1
Cited By
Energy-saving PET (Polyethylene Terephthalate) automobile roof and production process thereof
CN119898105A
High-purity composite carbon adsorption material as well as preparation method and application thereof
CN120001336A
Glue-free low-odor automobile roof and preparation method thereof
CN122100600A